The Improvement Of Ta’bir Syafahi By Implementing Arabic Instruction At UIN Syarif Hidayatullah Jakarta/ ترقية التعبير الشفهي من خلال جعل اللغة العربية لغة التدريس بجامعة شريف هداية الله الإسلامية الحكومية جاكرتا - Muchtar, Imamuddin; Bahruddin, Uril; Nurhadi, Nurhadi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
Students’ weak ability in speaking Arabic is still a challenge for many educational institutions. This happens due to the lack of students’ opportunities to use Arabic and Arabic speaking figures in the learning environment. This research aimed to investigate: (1) the application of Arabic instruction at UIN Syarif Hidayatullah Jakarta, (2) the supporting factors of success in improving Ta'bir Syafahi at UIN Syarif Hidayatullah Jakarta, (3) the positive implications of teaching using Arabic instruction towards students' language skills. Qualitative approach case study was employed in this research with interview and observation as the data collection techniques. Documentation during the study were also collected as a supporting instrument. Furthermore, the data analysis step was collecting, condensing, interpreting, concluding, and confirming the validity of the data by triangulation method and peer discussion. The results of this study indicated that: Firstly, the application of Arabic as the language of instruction at UIN Jakarta is represented in four curriculum components: objectives, material, methods, and learning evaluation. Secondly, there are two supporting factors for increasing Ta'bir Syafahi by suing Arabic instruction at UIN Syarif Hidayatullah Jakarta, they are the internal factors consisting of the students’ motivation and enthusiasm to make progress and the students’ background, and external factors consisting of training routines, supportive language environment, competent human resources, also material and non-material support from the faculty. Lastly, the positive implications of teaching using Arabic instruction towards students' language skills at UIN Syarif Hidayatullah Jakarta are divided into two areas: fluency and speaking confidence. In conclusion, the shaping of Arabic-speaking learning environment through the use of Arabic instruction can contribute to improve students’ ability of Ta'bir Syafahi.